In Search of the Holy Grail of Artificial Hearts: Are We There Yet? - Volod, Oksana; Colon, Modesto J.; Arabía, Francisco A. (Seminars in Thrombosis and Hemostasis, 2023)
The total artificial heart (TAH) has a long and rich history, being the product of decades of innovation, hard work, and dedication. This review examines the history of the TAH, a device that has revolutionized the treatment of end-stage biventricular heart failure. It reviews the development of the device from early concepts to the current state-of-the-art device, the SynCardia TAH, which has been implanted in over 2,000 patients worldwide. The article also discusses the challenges and successes experienced by researchers, clinicians, and patients throughout the development of TAH devices. Our focus will also be on discussing the hemostatic alterations in patients implanted with TAH and anticoagulation strategies to decrease associated thromboembolic risks. The article concludes with a look at other novel TAH devices and the future of TAH as an increasingly viable treatment for end-stage heart failure.
Keywords: total artificial heart; history; anticoagulation